Assessment and management of delirium in primary care. Issue 6 (November 2015) - Stephens, Jane
Abstract : Our commentaries from the Primary Care Neurology Society (P‐CNS) provide a primary care perspective on the neurology articles in Progress. Here, Dr Stephens considers 'An overview of delirium for the community and hospital clinician' (see p23).